Beginning drama 4-11 - Winston, Joe; Tandy, Miles (London ; New York : Routledge, 2009)
This third edition of 'Beginning Drama 4-11' is fully updated and revised in light of the renewed Framework for Teaching Literacy, and provides an introduction for early years and primary school teachers who are new to drama and for student teachers who wish to specialise in the teaching of drama
Includes bibliographical references and index.
Keywords: Drama in education; Drama -- Study and teaching (Elementary)